ANALISIS PENGARUH CASH RATIO, RETURN ON ASSETS, GROWTH, DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO (Studi Empiris Pada Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014) - Galih Nurcahyo (INVENTORY: JURNAL AKUNTANSI, 2017)
The purposive of this study was to determine whether effect of Cash ratio (CR), Return on Asset (ROA,) Growth, and Debt To Equity Ratio toward Dividend Payout Ratio in BUMN company period 2010-2014.The sampling method was done by using purposive sampling of 10 companies from population is 20 companies BUMN. The researched data was obtained from ICMD, and Financial Statements in 2010-2014. The data analysis technique is asumsi klasik testing, multiple linear regression, and Hypothesis testing. This research results that Return On Assets gives significantly positive on dividend payout ratio. While it indicates that Cash Ratio variable, and Debt to Equity Ratio partially positive and not significant toward Dividend Payout Ratio. Growth variable partially negatife and not significant toward Dividend Payout Ratio. Simultan test stated that all variables in this research has positive influence and significant to the Dividend Payout Ratio (DPR). Key words: Cash Ratio, Debt to Equity Ratio, Dividend Payout Ratio, Growth, Return on Assets